Provisioning and Operation of Virtual Networks - Meier, Sebastian; Barisch, Marc; Kirstädter, Andreas; Schlosser, Daniel; Duelli, Michael; Jarschel, Michael; Hoßfeld, Tobias; Hoffmann, Klaus; Hoffmann, Marco; Kellerer, Wolfgang; et al. (Electronic Communications of the EASST, 2011)
In today’s Internet, requirements of services regarding the underlying transport network are very diverse. In the future, this diversity will increase and make it harder to accommodate all services in a single network. A possible approach to keep up with this diversity in future networks is the deployment of isolated, custom tailored networks on top of a single shared physical substrate. The COMCON (COntrol and Monitoring of COexisting Networks) project aims to define a reference architecture for setup, control, and monitoring of virtual networks on a provider- and operator-grade level. In this paper, we present the building blocks and interfaces of our architecture.